Alternative splicing and parallel patterns of gene expression underlie population and life history divergence in an amphibian - Hu, Juntao; Ren, Xingyue; Barrett, Rowan; Samma, Eman; Sulkowski, Mikloaj; Brady, Steven (2025)
Keywords: Alternative splicing; Amphibian; Biology; Computational biology; Demography; Divergence (linguistics); Ecology; Evolutionary biology; Gene; Gene expression; Genetics; Life history; Messenger RNA; Population; RNA splicing; Sociology; dept.bio

Alternative Splicing and Gene Expression Variation Underlie Population and Life History Differences in an Amphibian - Hu, Juntao; Ren, Xingyue; Barrett, Rowan; Samma, Eman; Sulkowski, Mikolaj; Brady, Steven (Ecology and Evolution, 2025)
ABSTRACT Phenotypic variation is common across life history and among populations occupying different environments, yet the molecular mechanisms underlying these axes of divergence remain poorly understood. Much work has focused on gene expression as a link between genetic variation, environmental variation, and phenotypes, but post‐transcriptional processes such as alternative splicing—which affect how transcripts are assembled rather than how much of a transcript is produced—are increasingly recognized as additional modulators of plasticity and adaptation. Here, we examined gene expression and alternative splicing together in the wood frog ( Rana sylvatica ), an amphibian with a complex life cycle whose populations differ across replicated gradients of road adjacency and associated pollution. We found extensive transcriptomic differences between hatchlings and adults, with thousands of genes differentially expressed or spliced. Individuals clustered strongly by population for both expression and splicing. Differences at the habitat level were less extensive, but revealed two differentially expressed genes ( HSP70 and Gpsm2 ) and one differentially spliced gene ( Cd82 ) that consistently distinguished roadside and woodland populations. Overall, genetic differentiation between populations was low, suggesting that phenotypic and transcriptomic differences likely emerge in the presence of gene flow and reflect plastic responses. Together, these results highlight transcriptomic plasticity as an important mechanism shaping variation across both development and population differentiation.
Keywords: Alternative splicing; Amphibian; Gene; Gene expression; Genetic variation; Phenotypic plasticity; Population; Transcriptome; alternative splicing; dept.bio; gene expression; local adaptation; maladaptation; population divergence